Effects of Marijuana Legalization on Law Enforcement and Crime, Washington, 2004-2018 - Stohr, Mary ([Verlag nicht ermittelbar], 2021)
This study sought to examine the effects of cannabis legalization on crime and law enforcement in Washington State. In 2012 citizens voted to legalize possession of small amounts of cannabis, with the first licensed retail outlets opening on July 1, 2014. Researchers crafted their analysis around two questions. First, how are law enforcement agencies handling crime and offenders, particularly involving marijuana, before and after legalization? Second, what are the effects of marijuana legalization on crime, crime clearance, and other policing activities statewide, as well as in urban, rural, tribal, and border areas? Research participants and crime data were collected from 14 police organizations across Washington, as well as Idaho police organizations situated by the Washington-Idaho border where marijuana possession is illegal. Additional subjects were recruited from other police agencies across Washington, prosecutors, and officials from the Washington State Department of Fish and Wildlife, Washington State Liquor and Cannabis Board, and the National Association of State Boating Law Administrators for focus groups and individual interviews. Variables included dates of calls for service from 2004 through 2018, circumstances surrounding calls for service, geographic beats, agency, whether calls were dispatch or officer initiated, and whether the agency was in a jurisdiction with legal cannabis.